A Subset of Equine Gastric Squamous Cell Carcinomas Is Associated With Equus Caballus Papillomavirus–2 Infection. Issue 3 (May 2020) - Alloway, Elizabeth; Linder, Keith; May, Susan; Rose, Trevor; DeLay, Josepha; Bender, Susan; Tucker, Alison; Luff, Jennifer
Squamous cell carcinoma (SCC) is the most common neoplasm of the equine stomach. However, the mechanisms underlying malignant transformation are unknown. As Equus caballus papillomavirus–2 (EcPV-2) is a likely cause of some genital SCCs, we hypothesized that EcPV-2 is associated with a subset of equine gastric SCCs. To this aim, we performed polymerase chain reaction (PCR) and in situ hybridization (ISH) for EcPV-2 E6/ E7 oncogenes on 11 gastric SCCs and on gastric samples from 15 control horses with no SCC. PCR for EcPV-2 was positive in 7/11 (64%) gastric SCCs; non-SCC gastric samples were all negative. Intense hybridization signals for EcPV-2 E6/E7 nucleic acid were detected by ISH within tumor cells in 5/11 (45%) gastric SCCs, including distant metastases. No hybridization signals were detected within any of the non-SCC gastric cases. This study provides support for a potential association between EcPV-2 infection and a subset of equine gastric SCC.